Jesus as Interceding High Priest and Sacrifice in Hebrews: A Response to Nicholas Moore - Moffitt, David M. (Journal for the study of the New Testament, 2020)
Is Jesus’ perpetual intercession for his people in Hebrews (Heb. 7.25) understood as a constitutive part of his atoning, high-priestly ministry? Nicholas Moore argues that Jesus’ act of sitting at God’s right hand is the decisive end of Jesus’ atoning sacrifice and so also of Hebrews’ Yom Kippur analogy. Among other points, I argue in response that Jesus’ ongoing absence from his people, status as high priest and current location in the heavenly holy of holies imply that Hebrews’ Yom Kippur analogy extends beyond Jesus’ act of sitting to include his present ministry of intercession. Not only were prayer and atoning sacrifice closely correlated for Second Temple Jews, Hebrews presents Jesus as the high priest who, in his resurrected humanity, is always also the sacrifice in the Father’s presence. Jesus presented himself to the Father once, but he is perpetually the high priest and sacrifice who ministers in God’s presence. For Hebrews, the Yom Kippur analogy (and so also Jesus’ atoning ministry) ends when, like the earthly high priests, Jesus leaves the heavenly holy of holies to return to and again be present with his people (Heb. 9.28). Only then will his followers receive the salvation for which they are waiting. Until that approaching day arrives, Jesus’ ongoing intercession with his Father ensures that his people will be saved completely.